Pengembangan Vaksin Inaktif Tetelo Genotipe VII Isolat Lokal pada Kondisi Laboratorium. (DEVELOPMENT OF TETELO INACTIVATED VACCINE GENOTYPE VII LOCAL ISOLATE IN LABORATORY CONDITION) - Indriani, Risa; Dharmayanti, Ni Luh Putu Indi (Jurnal Veteriner; Vol 17 No 3 (2016), 2016)
Tetelo/Newcastle disease (ND) inactive vaccine of genotipe VII virus local isolate have been developedin laboratory condition and compared with commercial ND vaccine. A total of 200 commercial layer chickenat 4 weeks age were divided into four groups, that were (1) vaccinated with ND genotype VII Indonesia/GTT/11, (2) vaccinated with commercial ND vaccine genotype VII, (3) vaccinated with commercial genotypeVI and (4) unvaccinated as control group. After two weeks post vaccination, 10 chicken from each groupwere sellected randomly and challenged with 105 EID50 per 0,1 mL of ND virus genotype VII Indonesian/GTT/11 by intramuscular. Chicken were observed, and swab were collected from oropharyngeal and cloacaat 2, 5, 7, 12 and 14 days post challenge. The result of this study showed inactived vaccine genotype VIIIndonesia/GTT/11 can induced a good antibody titer response to vaccinated chicken with mean titer 7.30log2 and CI 6.3 to 7.8, while commercial ND vaccine genotipe VII was 5.30 log2 with CI 3.8-6.7, andcommercial genotype VI was 4.8 log2 with CI 4.1-5.4. The level of protection which determined by noclinical signs, mortality and viral shedding showed 100% protection in chicken vaccinated with Indonesia/GTT/11 and commercial genotype VII were 100%, compared with control chicken, and vaccined commercialND vaccine genotype VII, compared with control chicken. While in chicken vaccinated commercial NDvaccine genotype VI showed viral shedding on day two post challenge, but there were no clinical sign andmortality. Based on this results, Indonesia/GTT/11 genotype VII ND vaccine could be used as an alternativeND vaccine to protect chicken from infection of ND virus genotype VII in the field.
Keywords: tetelo/Newcastle disease, local, genotype, seed, vaccine